PENGARUH PENGENDALIAN INTERN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT JAYA SELULAR INDONESIA (VIVO SMARTPHONE) - Diapati, Mutiara Mashita; Diarespati, Diarespati; Munayang, Olivia H (Jurnal Metaverse ADPERTISI, 2024)
This study aims to determine the effect of internal control and compensation on employeeperformance at PT. Jaya Selular Indonesia (VIVO Smartphone) Palu Branch. The researchmethod used is a verifiative survey research method, to be able to provide an accurate and clearpicture of the effect of internal control and compensation on employee performance at PT. Jayaselular Indonesia (VIVO Smartphone) Palu branch. The sample in this study amounted to 67respondents who were distributed to employees of PT. Jaya Selular Indonesia (VIVO Smartphone)Palu Branch. The data analysis method used is multiple linear analysis. Based on the results ofdata processing using the SPSS for windows version 16.0 program, research results were obtainedwhich showed that internal control and compensation simultaneously had a significant effect onemployee performance. Internal control does not have a significant effect on performance andcompensation partially has a significant effect on employee performance. The influence of theoverall independent variable, addressed by the adjusted R square value of 0.494, can beinterpreted that the variables of internal control and compensation have an effect of 49.4% onemployee performance at PT. Jaya Selular Indonesia (VIVO Smartphone) Palu Branch.While theremaining 50.1% was influenced by other variables that were not studied in this study